Graduate-Level Public Sector Accounting: Status and Forecast. - Holder, William W. (The Accounting Review, 1978)
Abstract ABSTRACT: This study was concerned with Graduate-Level Public Sector Accounting Education (GLPSA) in the United States. A survey was conducted of the 123 graduate MBA programs currently accredited by the American Assembly of Collegiate Schools of Business, with 81 responses (65.8 percent received. From the responses, it was determined that 11 schools currently offer a GLPSA course, while an additional 40 schools are planning such a course for offering within the next five years. Various reasons were suggested by the 70 institutions currently not offering a GLPSA course such as a lack of resources, inadequate student and faculty interest, and low employment opportunities. Schools currently offering a GLPSA course were requested to return a copy of the course syllabus. Analysis of the 11 syllabi received revealed that most of the courses presently offered consider primarily financial accounting and reporting issues related to such public sector entities as municipalities, hospitals, colleges and universities, etc. Although most courses did consider such issues as budgeting and managerial control, the time devoted to these topics generally was limited to a small portion of the course.